2008
DOI: 10.1159/000113306
|View full text |Cite
|
Sign up to set email alerts
|

Giardiasis: Modern Concepts in Control and Management

Abstract: Giardia is the most common enteric protozoan pathogen of humans, domestic animals and wildlife. Children are at the most risk from the clinical consequences of Giardia infection, particularly those in developing countries and living in disadvantaged community settings. Molecular epidemiological studies have helped to elucidate sources of infection and the public health significance of animal reservoirs. Although aspects of the pathogenesis of Giardia infection are now understood, we are still a long way from u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 81 publications
0
8
0
3
Order By: Relevance
“…; most of these can be attributed to deficiencies in the filtration process (THOMPSON, 2004;KARANIS et al, 2007;BALDURSSON;KARANIS, 2011;EFSTRATIOU et al, 2017). Cattle has already been considered as a source of water contamination; however, there is little evidence that these animals are the main source of waterborne outbreaks, and that contamination with sanitary effluent from domestic sources is the most likely source (THOMPSON, 2004;SMITH et al, 2006;THOMPSON, 2008). Livestock and rainfall in poorly filtered catchment areas favor the occurrence of outbreaks, especially in areas where environmental concentrations of these protozoans are higher (RISEBRO et al, 2007;PLUTZER et al, 2010a).…”
Section: Cryptosporidium and Giardia: Waterborne Organisms And Their mentioning
confidence: 99%
“…; most of these can be attributed to deficiencies in the filtration process (THOMPSON, 2004;KARANIS et al, 2007;BALDURSSON;KARANIS, 2011;EFSTRATIOU et al, 2017). Cattle has already been considered as a source of water contamination; however, there is little evidence that these animals are the main source of waterborne outbreaks, and that contamination with sanitary effluent from domestic sources is the most likely source (THOMPSON, 2004;SMITH et al, 2006;THOMPSON, 2008). Livestock and rainfall in poorly filtered catchment areas favor the occurrence of outbreaks, especially in areas where environmental concentrations of these protozoans are higher (RISEBRO et al, 2007;PLUTZER et al, 2010a).…”
Section: Cryptosporidium and Giardia: Waterborne Organisms And Their mentioning
confidence: 99%
“…The clinical impact of Giardia is the greatest in children, particularly in developing countries or disadvantaged communities where poor hygiene and the proximity of animal reservoirs sustain environmental contamination leading to a high frequency of transmission and the establishment of chronic infections (Thompson, 2008). In such situations, nutrition may be suboptimal, exacerbating the impact of Giardia infections that contribute to poor growth and development (failure to thrive) in early childhood, zinc and iron deficiency, poor cognitive function, and failure to thrive (growth retardation) as well as predispose to the development of allergic diseases (Berkman et al, 2002 andreviewed in Savioli et al, 2006;Thompson, 2008.…”
Section: Giardiamentioning
confidence: 99%
“…Drugs are not the answer as studies have shown that once drug pressure is removed without concurrent improvements in hygiene and sanitation, reinfection rapidly occurs (Thompson et al, 2001;Thompson, 2008). Long-term freedom from infection requires education in terms of basic hygiene, but without improvement in sanitation it is difficult to see how the impact of enteric parasite infections can be improved.…”
Section: Control and Future Trendsmentioning
confidence: 99%
“…In non-fatal cases of diarrhea, particularly chronic infections diarrhea has been strongly correlated with growth retardation and yet good health is a precondition for society to develop. (Prado et al ., 2005; Thompson, 2008; Tumwine et al ., 2003)…”
Section: Introductionmentioning
confidence: 99%